Electrochemical Degradation of Industrial Textile Dye Disperse Yellow 3 Role of Electrocatalytic Material and Experimental Conditions on the Catalytic Production of Oxidants and Oxidation Pathway - Ureta-Zanartu, M; Salazar-Gonzalez, R; Gonzalez-Vargas, C; Gonzalez-Vargas, C (Elsevier Ltd, 2018)
This study aimed to verify the efficiency of the electrochemical oxidation process for removal the industrial textile Disperse Yellow 3 (DY3) dye in aqueous solutions using different electrocatalytic materials: boron-doped diamond (BDD), Ti/Ru0.3Ti0.7O2 and Ti/Pt anodes. The results were obtained by applying different current densities (40 and 60 mA cm−2) at 40 °C using different supporting electrolytes (Na2SO4 50 mM and NaCl 50 mM) under values of pH about 2.3, 7.0 and 10.0. Results obtained shown that the process was faster at the beginning of the process for all electrocatalytic materials, using Na2SO4 as electrolyte, being more efficient for BDD anode reaching more than 90% of TOC and color decay independently of the current density and pH and supporting electrolyte; while up to 50% of color and TOC was eliminated, using the other anodic materials in sulfate. In NaCl medium a complete mineralization was achieved at Ti/Ru0.3Ti0.7O2 at short electrolysis time, followed by BDD and Ti/Pt. The corresponding kinetic analysis confirms these results. Trends of active chlorine species synthesized at Ti/Ru0.3Ti0.7O2, BDD and Ti/Pt anodes, at different pH conditions, demonstrated that, the concentration of active chlorine species depends on the pH conditions and electrode material. Finally, a cost comparison for each electrocatalytic material under different experimental conditions was realized exhibiting the lowest energy consumption and electrolysis time in NaCl medium. Based on the results obtained, the electrochemical elimination of dye and the profile of the carboxylic by-products formed depend on the nature of material, pH and supporting electrolyte. © 2017 Elsevier Ltd